Analisis sistem instrumen intensity meter p-alert dan data hasil pengukurannya (System analysis of the intensity meter p-alert instrument and its measurement data) - Yeni Rahman; Zulhendri Kamus; Rachmad Billyanto (Department of Physics – Universitas Negeri Padang UNP, 2015)
Earthquake would cause ground acceleration. To the ground acceleration can be measured by using intensity meter p-alert instrument. Instrument compiled of sensor, modem, hub D-Link, and display. This research to describe the constituent components and data analysis. The sensor used in instrument is triaxial MEMS accelerometer ADIS16223 and digital signal processing component used microcontroler MaximMAX7219 with RJ45 data communication. Data analysis of peak ground acceleration for five times earthquakes use P-Alert Early Warning software